Soluble ceramic core for in-situ growth of mullite whiskers by using low-grade ball clay

By using low-grade ball clay and sodium chloride in the ceramic core, mullite whiskers are grown in situ, which solves the problems of low strength and easy breakage of the ceramic core, and achieves high strength, high toughness and good collapse. , suitable for precision casting.

CN119430863AActive Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202411259959.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-14
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

During the casting process, existing ceramic cores have problems such as low strength, easy to break, high brittleness, low toughness and difficulty in dissolution, which affects the quality of the castings.

Method used

Low-grade ball clay is used as raw material, and sodium chloride is added as a binder and whisker additive to grow mullite whiskers in situ during medium temperature sintering, enhancing the strength, toughness and impact resistance of the ceramic core.

Benefits of technology

It achieves high strength, high toughness, good heat and mechanical impact performance of the ceramic core, and is not easy to crack during sintering, has a high yield, a smooth surface, and has good collapse properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430863A_ABST
    Figure CN119430863A_ABST
Patent Text Reader

Abstract

The invention discloses a soluble ceramic core for in-situ growth of mullite whiskers by using low-grade ball clay. The soluble ceramic core is prepared from the following raw materials: low-grade ball clay, sodium chloride and water. The method comprises the following steps: drying and sieving low-grade ball clay, then mixing with sodium chloride, adding water, carrying out spray granulation, putting into a mold, carrying out compression molding, transferring into a muffle furnace, heating to 300 DEG C at a rate of 5 DEG C / min, carrying out heat preservation for 0.5 h, heating from 300 DEG C to 725-775 DEG C at a rate of 3 DEG C / min, sintering for 1.0 h, then cooling to 100 DEG C, and taking out to obtain the in-situ growth mullite whisker soluble ceramic core. The core is manufactured through the pressing sintering technology, the technology is simple, mullite whiskers grow in situ in the ceramic core in the sintering process, the soluble ceramic core is reinforced and toughened, sodium chloride serves as a binder, pollution is avoided, and the comprehensive performance is excellent. The bending strength is 7-15 MPa, the tensile strength is 2-6 MPa, and the material can be collapsed at the water temperature of 90 DEG C, so that a new technology is provided for ceramic mold casting development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic cores, in particular to a soluble ceramic core used for ceramic casting. Background Art

[0002] With the development of the automobile industry, the demand for castings with complex inner cavities has gradually increased. Traditional organic resin sand cores have problems such as low strength, large gas emission, large environmental pollution, and poor disintegration. The wall of the mold required for precision casting is very thin. During the metal liquid casting process, due to low strength, the existing resin sand core is difficult to withstand the erosion and corrosion of the metal liquid, resulting in defects such as cracks and pores, which affect the quality of the casting. At present, there are soluble or easily disintegrated ceramic cores, which have the advantages of high temperature resistance and corrosion resistance. The fiber structure inside makes the collapsed core easy to clean. It can be applied to complex inner cavity structure casting mold technology. There is a relative lack of technology. The ceramic cores obtained by the existing technology generally have the disadvantages of high brittleness, low toughness, and easy fracture.

[0003] Fiber-reinforced ceramic matrix composites (CMC) are materials that add fibers to a ceramic matrix to increase strength and toughness. They have been widely used in aerospace, transportation, defense and military industries. The fibers used in fiber-reinforced ceramic matrix composites can be divided into continuous fibers, chopped fibers and whiskers. There are two main methods for whisker-toughened ceramic composites: the external whisker method and the in-situ whisker growth method. The in-situ whisker growth method is to mix ceramic powder and whisker growth aids, and prepare a ceramic core containing whiskers under certain conditions. This patent uses low-grade ball clay as a refractory material and sodium chloride as a growth aid. Through sintering, a ceramic composite material containing mullite whiskers is prepared. Ball clay mainly contains kaolinite and quartz. High-grade ball clay has a kaolin content of more than 80% and a tailings content of less than 20%. High-grade ball clay is a type of high-quality refractory material. This type of ball clay has the advantages of fine particle size, strong plasticity, good adhesion, high dry strength, wide firing range, high refractoriness, and not easily corroded by metal liquids. It can be used as a ceramic raw material, but as a ceramic core, it is difficult to collapse after firing. Low-grade ball clay contains more than 20% quartz components, and some even reach 40%. Low-grade ball clay often contains feldspar and other clay minerals, and its kaolinite content is less than 80%, so it cannot be directly used as a refractory raw material, but as a raw material for ceramic cores, it can provide better collapse. At this stage, low-grade ball clay is regarded as a "solid waste" from ball clay mining, and backfilling is usually used for digestion. The tailings of low-grade ball clay are very fine (2-30μm) and uneven in particle size. As a raw material for ceramic cores, it is not only conducive to sintering, but also greatly provides collapseability. Because low-grade ball clay contains a certain amount of kaolin, which provides a smooth surface for metal casting, low-grade ball clay is an excellent raw material for ceramic casting.

[0004] Patent document CN109574636A discloses a water-soluble ceramic core for investment casting of aluminum alloy and its preparation method, wherein the base material of the water-soluble ceramic core is corundum powder, the mineralizer is quartz powder, sodium chloride and potassium chloride, wherein the corundum powder is 40-50%, the mineralizer is 50-60%, and the plasticizer is paraffin, beeswax, etc. The method compresses the plasticizer and pure corundum powder, and then roasts, dewaxes, and finally burns, but the technology uses pure corundum powder, which is more expensive and has poor surface finish of the casting. Patent text CN114850412A discloses a hot die casting water-soluble ceramic core for light alloy investment casting, which also uses raw materials such as fused corundum powder, potassium sulfate, plasticizer, lubricant and surfactant, and the weight ratio is 60-80:7.7-30:10-15:1-2:1-2, and the ingredients include paraffin, beeswax, polyethylene, stearic acid and oleic acid, and the weight ratio is 90-95:2-4:2-4:1-2:1-2. Both of the above patents use plasticizer paraffin or beeswax to improve the plasticity of the original embryo. In the process of dewaxing and sintering, the decomposition of organic matter inevitably pollutes the environment, and wax-based plasticization leads to stress concentration. In the degreasing process, the green embryo is prone to collapse and deformation and other defects, deformation and other weaknesses. This patent uses low-grade ball clay as raw material, and utilizes its strong plasticity to press green bodies with higher strength without adding additional plasticizers. Therefore, this patent is different from the above patents in properties such as raw material source, plastic processing method, and green body reinforcement mechanism.

[0005] Patent CN102786295A discloses a method for preparing a soluble ceramic core, which uses fused corundum, zircon sand, and sodium chloride particles as the main body, sodium chloride solution and polyethylene glycol as binders, and obtains a water-soluble core ceramic core by mixing, low-temperature drying, and high-temperature roasting at 920°C. Patent text CN105693254A discloses a water-soluble ceramic core material, which uses high-temperature resistant ceramics as raw materials, adds water-soluble inorganic salts and metal oxides, and adds at least one amorphous ceramic material. In this method, the mass fraction of water-soluble inorganic salts is 10% to 50%, the mass fraction of water-soluble metal oxides is 2% to 50%, the mass fraction of amorphous ceramic materials is 0.1% to 30%, and the remainder is high-temperature resistant ceramic materials. The green body is pre-fired at 800℃-1000℃ for 2-5h, the water-soluble metal oxide is pre-fired at 800℃-1000℃ for 1-5h, the amorphous ceramic material is pre-fired at 500℃-800℃ for 2-5h, and the mixed material is finally fired to form a ceramic core. The raw materials used in the above two patents need to be pre-fired, and the mixed material is then re-fired, so high energy consumption is one of its weaknesses. In addition, the above method does not consider the source of raw materials and the comprehensive utilization of "solid waste" resources, and its practical application is limited. This patent directly uses low-grade ball clay as raw material, sintered at a lower temperature, and the raw materials do not need to be pre-fired, which can effectively utilize low-grade ball clay and promote resource utilization.

[0006] Patent text CN106927798A discloses a water-soluble ceramic core and a preparation method thereof, wherein the raw material composition is 100-120 parts of fused corundum, 20-40 parts of inorganic salt (20-30 parts of sodium chloride, 5-75 parts of sodium carbonate, 5-75 parts of potassium carbonate), and the water-soluble ceramic core is obtained by ball milling, pressing, and sintering at 720-750°C for 1-1.5h. Patent text CN110240471A discloses a water-soluble ceramic core and a preparation method thereof, wherein the raw material composition of the water-soluble ceramic core is 85-120 parts of quartz glass powder, 22-45 parts of water-soluble inorganic salt, wherein the water-soluble inorganic salt is one or a combination of sodium carbonate or potassium carbonate, ground and mixed in proportion, then pressed into shape, demolded, and then the embryo is calcined at 650°C-900°C for 0.5-1.5h to obtain a water-soluble ceramic core. The above two patent documents do not incorporate plastic refractory clay, the plasticity of the green body is poor, and the surface of the finished product is rough, which is not conducive to precision casting. Patent text CN117383916A discloses a soluble ceramic core, a preparation method and an application. The method comprises the following steps: uniformly mixing ceramic powder and soluble salt, and using a droplet jet bonding molding process to print out a ceramic core blank. After solidification, infiltration and drying, a ceramic core blank is obtained. The ceramic blank is placed in a high-temperature sintering furnace for sintering, and the soluble ceramic core is obtained after cooling with the furnace. Patent text CN105777114A discloses a preparation method for a soluble ceramic core. The water-soluble ceramic core comprises the following ingredients in a mass ratio: 20%-60% sodium chloride powder and 40%-80% zircon powder, wherein the total mass fraction of sodium chloride powder and zircon powder is 100%, and the total weight fraction of ethyl silicate and 15%-20% of plasticizer are added, wherein the plasticizer comprises 50% polyethylene glycol, 30% baking soda and 10% talcum powder. The above two patents remove organic precursors by pressing, dewaxing or sintering, and their high chemical substances cause the dual difficulties of high cost and environmental pollution. Patent text CN107042309B discloses a water-soluble core component and a preparation method thereof, wherein the raw material of the water-soluble ceramic core is composed of 40-80% chloride salt, 10-30% carbonate and 5-30% ceramic powder, wherein the ceramic powder is one or a combination of aluminum oxide powder, zirconium oxide powder and silicon oxide powder, and the carbonate is one or a combination of potassium carbonate and sodium carbonate; the ceramic core is prepared by injection molding, the molding temperature is 155℃-180℃, and after degreasing, it is sintered at 450℃-550℃ to obtain a water-soluble ceramic core; Patent text CN107262661A discloses a high temperature resistant and high strength water-soluble core and a preparation method thereof, wherein the mass percentage of the ingredients of the water-soluble core is 75%-95% of water-soluble salt, 5%-25% of ceramic material, and 0-5% of additive.The water-soluble salts include any one or more of potassium sulfate, sodium sulfate, and magnesium sulfate, the ceramic materials include any one or more of aluminum nitride, titanium nitride, tantalum nitride, boron nitride, aluminum boron nitride, and silicon nitride, and the additives include any one or more of polyvinyl alcohol, polyvinyl pyrrolidone, and water glass. Therefore, the above-mentioned patent drafts are still based on aluminum-based or other transition metal refractory powders, which have poor plasticity, difficult molding, rough surface, and are not conducive to precision casting. The decomposition of sulfates and the like will form acid mist, causing pollution. In the degree thesis (Effect of Refractory Aggregate-Based Binders on the Performance of Water-Soluble Ceramic Cores, Lebao, 2022), fused corundum powder and mullite powder were used as refractory aggregates, sodium chloride was used as a binder, and the cores were prepared by pressing and molding. The performance of the ceramic cores at sintering temperatures of 775°C, 800°C, and 825°C was studied. It was found that when the sintering temperature of the ceramic core was 800°C and 825°C, the addition of sodium chloride was 20wt.%, and the core strength was higher. However, the ceramic core of this method has defects such as high brittleness and easy cracking, poor impact resistance, and lack of fiber toughening measures. Therefore, the plasticity of the raw materials and finished products cannot meet the needs of precision casting. This patent uses low-grade ball clay as raw material, which has both plastic clay and quartz sand particles, and adds sodium chloride as a binder and whisker additive to form mullite whiskers inside the ceramic core. This whisker is a kind of excellent high-temperature resistant material, which makes the prepared soluble ceramic core surface smooth and corrosion-resistant, with high strength and toughness, and the finished product has excellent thermal shock resistance.

[0007] The present invention can utilize low-grade ball clay resources and effectively digest the "solid waste" of existing mines. This technology aims at the technical problems of strength, toughness, impact resistance and easy cracking of ceramic cores. Low-grade ball clay with different tailings contents is used as raw material, sodium chloride is used as whisker additive and binder, and mullite whiskers are generated in situ inside the calcined ceramic core through medium-temperature calcination (<800°C), so as to enhance the strength, toughness and impact resistance of the product. The product is not easy to crack during the calcination process and has a high yield rate. The raw materials used in this technology contain plastic ball clay, so the surface of the obtained product is smooth, with extremely high fire resistance and corrosion resistance, and does not react with molten metal. The sample has the advantages of high strength, high modulus, corrosion resistance, thermal vibration resistance, and mechanical impact resistance. The obtained core plate is immersed in water, and its sodium chloride is dissolved, which has good disintegration, ensuring the efficient disintegration of the mold. Therefore, the ceramic core obtained by this method can achieve precision casting and has excellent comprehensive performance. Summary of the invention

[0008] The present invention utilizes low-grade ball clay to prepare ceramic cores, effectively digesting the "solid waste" of ball clay mines.

[0009] The invention provides a soluble ceramic core using low-grade ball clay to in-situ grow mullite whiskers. Ultrafine quartz sand in the low-grade ball clay is used to calcine and form fibrous mullite whiskers, thereby improving the strength, toughness, heat resistance and mechanical impact performance of the ceramic core.

[0010] The present invention provides a soluble ceramic core for in-situ growth of mullite whiskers using low-grade ball clay, which utilizes plastic ball clay without adding additional plasticizers, thus solving the pollution caused by adding paraffin wax, beeswax, etc. during the sintering process. Technical solution:

[0011] In order to achieve the above technical requirements, the present invention provides a soluble ceramic core for in-situ growth of mullite whiskers using low-grade ball clay, which is achieved through the following technical solutions:

[0012] A soluble ceramic core for in-situ growth of mullite whiskers using low-grade ball clay is prepared from water and the following components: low-grade ball clay with different tailings contents and sodium chloride.

[0013] The invention provides a soluble ceramic core using low-grade ball clay to in-situ grow mullite whiskers. The raw materials mainly include low-grade ball clay with different quartz contents. The invention has no other special restrictions on the source of the low-grade ball clay used.

[0014] The present invention also provides an in-situ grown mullite whisker soluble ceramic core and a preparation method thereof, comprising the following steps:

[0015] (1) Low-grade ball clay with different quartz contents is dried in an oven at 110° C., and then sieved for use; non-mineral impurities such as branches are removed, and low-grade ball clay with a mass fraction of 70-90% (including quartz or tailings content of 40-70%) and sodium chloride with a mass fraction of 10-30% are mixed and ball-milled for 2-4 hours.

[0016] (2) The ball-milled ingredients are subjected to spray granulation, and 5-8% of water is added based on the weight of the ingredients.

[0017] (3) placing the above ingredients in a closed, light-proof environment at room temperature for aging for more than 24 hours to ensure that the water is evenly dispersed;

[0018] (4) Put the above ingredients into a mold, pound them using a hydraulic press (450 kN, 5.0 min), take them out, and dry them at room temperature for 10.0-12.0 h to obtain a green body;

[0019] (5) After the green body is dried, the temperature is raised to 300°C at a rate of 5°C / min and kept at this temperature for 0.5h. The temperature is then raised from 300°C to 725-775°C at a rate of 3°C / min and sintered for 1.0h. Finally, the temperature is lowered to about 100°C and taken out, thereby obtaining a soluble ceramic core with in-situ growth of mullite whiskers using low-grade ball clay.

[0020] Positive effects of the present invention:

[0021] The present invention provides a soluble ceramic core using low-grade ball clay to grow mullite whiskers in situ, and the positive effects are:

[0022] 1. A soluble ceramic core that uses low-grade ball clay to grow mullite whiskers in situ. By adding sodium chloride to react with quartz in the low-grade ball clay, medium-temperature sintering below 800°C can be achieved. While saving energy, mullite whiskers can also be grown in situ, greatly enhancing the strength, toughness and impact resistance of the ceramic core.

[0023] 2. A soluble ceramic core that uses low-grade ball clay to in-situ grow mullite whiskers. By utilizing the plasticity of the low-grade ball clay, the high temperature resistance and corrosion resistance of the mold are ensured, a smooth surface is obtained, and the precise size requirements of the casting are guaranteed.

[0024] 3. A soluble ceramic core using low-grade ball clay to grow mullite whiskers in situ. The prepared ceramic core has good disintegration properties. Under a water temperature of 90°C, the core is leached for 1.8-2 hours to achieve core removal and disintegration, making it easy to clean the casting. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of a ceramic core according to an embodiment of the present invention.

[0026] Figure 2 This is a schematic diagram after collapse of one embodiment of the present invention.

[0027] Figure 3 This is a core fracture scan according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described by way of the following examples, which do not limit the present invention in any way. Without departing from the technical solution of the present invention, any modification or change made to the present invention that is easily implemented by a person of ordinary skill in the art will fall within the scope of the claims of the present invention.

[0029] Embodiment 1:

[0030] The batch composition is 90% by weight of low-grade ball clay (of which the quartz content in the tailings is 40%), 10% of sodium chloride; 8% of water is added; the mixture is fully and evenly mixed and dispersed, placed in a closed light-proof environment at room temperature, and allowed to stand for more than 24 hours to ensure uniform moisture; after being taken out, the mixture is evenly placed in a mold, pounded with a hydraulic press (450 kN, 5.0 min), taken out, and dried at room temperature for 10.0-12.0 h; the dried sample is placed in a muffle furnace and heated to 300° C. at a rate of 5° C. / min and kept warm for 0.5 h, then heated from 300° C. to 725° C. at a rate of 3° C. / min and sintered for 1.0 h, then cooled to about 100° C. and taken out.

[0031] Embodiment 2:

[0032] The batch composition is 80% by weight of low-grade ball clay (of which the quartz content in the tailings is 60%), 20% of sodium chloride; 7% of water is added; the mixture is fully and evenly mixed and dispersed, placed in a closed light-proof environment at room temperature, and allowed to stand for more than 24 hours to ensure uniform moisture; after being taken out, the mixture is evenly placed in a mold, pounded with a hydraulic press (450 kN, 5.0 min), taken out, and dried at room temperature for 10.0-12.0 h; the dried sample is placed in a muffle furnace and heated to 300° C. at a rate of 5° C. / min and kept warm for 0.5 h, then heated from 300° C. to 725° C. at a rate of 3° C. / min and sintered for 1.0 h, then cooled to about 100° C. and taken out.

[0033] Embodiment 3:

[0034] The batch composition is 70% by weight of low-grade ball clay (of which the quartz content in the tailings is 50%), 30% of sodium chloride; 6% of water is added; the mixture is fully and evenly mixed and dispersed, placed in a closed light-proof environment at room temperature, and allowed to stand for more than 24 hours to ensure uniform moisture; after being taken out, the mixture is evenly placed in a mold, pounded with a hydraulic press (450 kN, 5.0 min), taken out, and dried at room temperature for 10.0-12.0 h; the dried sample is placed in a muffle furnace, heated to 300° C. at a rate of 5° C. / min, and kept warm for 0.5 h, then heated from 300° C. to 725° C. at a rate of 3° C. / min, sintered for 1.0 h, and then cooled to about 100° C. and taken out.

[0035] Embodiment 4:

[0036] The batch composition is 70% by weight of low-grade ball clay (of which the quartz content in the tailings is 55%), 30% of sodium chloride; 5.5% of water is added; the mixture is fully and evenly mixed and dispersed, placed in a closed light-proof environment at room temperature, and allowed to stand for more than 24 hours to ensure uniform moisture; after being taken out, the mixture is evenly placed in a mold, pounded with a hydraulic press (450 kN, 5.0 min), taken out, and dried at room temperature for 10.0-12.0 h; the dried sample is placed in a muffle furnace, heated to 300° C. at a rate of 5° C. / min, and kept warm for 0.5 h, then heated from 300° C. to 725° C. at a rate of 3° C. / min, sintered for 1.0 h, and then cooled to about 100° C. and taken out.

[0037] Embodiment 5:

[0038] The batch composition is 80% by weight of low-grade ball clay (of which the quartz content in the tailings is 65%), 30% of sodium chloride; 7% of water is added; the mixture is fully and evenly mixed and dispersed, placed in a closed light-proof environment at room temperature, and allowed to stand for more than 24 hours to ensure uniform moisture; after being taken out, the mixture is evenly placed in a mold, pounded with a hydraulic press (450 kN, 5.0 min), taken out, and dried at room temperature for 10.0-12.0 h; the dried sample is placed in a muffle furnace, heated to 300° C. at a rate of 5° C. / min, and kept warm for 0.5 h, then heated from 300° C. to 750° C. at a rate of 3° C. / min, sintered for 1.0 h, and then cooled to about 100° C. and taken out.

[0039] Embodiment 6:

[0040] The batch composition is 80% by weight of low-grade ball clay (of which the quartz content in the tailings is 70%), 30% of sodium chloride; 7% of water is added; the mixture is fully and evenly mixed and dispersed, placed in a closed light-proof environment at room temperature, and allowed to stand for more than 24 hours to ensure uniform moisture; after being taken out, the mixture is evenly placed in a mold, pounded with a hydraulic press (450 kN, 5.0 min), taken out, and dried at room temperature for 10.0-12.0 h; the dried sample is placed in a muffle furnace, heated to 300° C. at a rate of 5° C. / min, and kept warm for 0.5 h, then heated from 300° C. to 775° C. at a rate of 3° C. / min, sintered for 1.0 h, and then cooled to about 100° C. and taken out.

[0041] Test example:

[0042] The performance of a soluble ceramic core prepared in Example 1-6 using low-grade ball clay to grow mullite whiskers in situ was tested, and the test results are as follows:

[0043] Table 1 Ceramic core performance test

[0044]

[0045] As shown in Table 1, the performance of Examples 1 to 6 is that the flexural strength is ≥6MPa, and the tensile strength is ≥3Mpa. All of the examples can meet the enterprise standards.

Claims

1. A soluble ceramic core using low-grade ball clay to grow mullite whiskers in situ, characterized in that: The ingredients of the soluble ceramic core are: 70-90% by mass of low-grade ball clay, 10-30% by mass of sodium chloride, and 5-8% by mass of water of the added ingredients.

2. The method of in-situ growing mullite whisker soluble ceramic core using low-grade ball clay according to claim 1, characterized in that: The ball clay tailings content in the low-grade ball clay is 40-70%.

3. A method for preparing a soluble ceramic core using in-situ growth of mullite whiskers using low-grade ball clay according to claim 1 or 2, wherein the specific implementation steps are: (1) drying low-grade ball clay in an oven at 110° C. and then sieving for later use; taking 70-90% by mass of low-grade ball clay, 40-70% of the quartz content in its tailings, taking 10-30% by mass of sodium chloride, mixing and ball milling for 2-4 hours; (2) spray granulating the ball-milled ingredients and adding 5 to 8% water by weight; (3) placing the composite material in a closed, light-proof environment at room temperature for aging for more than 24 hours to ensure that the water is evenly dispersed; (4) Put the above composite material into the mold, use a hydraulic press to pound it and take it out, the pressure is about 450 kN, and the pressure is maintained for about 5.0 minutes to obtain a ceramic core with a certain size and properties, and then dry it at room temperature for 10.0-12.0 hours for use; (5) The dried sample is placed in a muffle furnace and heated to 300°C at a rate of 5°C / min and kept at this temperature for 0.5h. Then, the sample is heated from 300°C to 725-775°C at a rate of 3°C / min, sintered for 1.0h, and then cooled to about 100°C and taken out to obtain a soluble ceramic core for in-situ growth of mullite whiskers using low-grade ball clay.

Citation Information

Patent Citations

  • Water-soluble ceramic core material and preparation method thereof

    CN105693254A

  • Preparation method of water-soluble ceramic core

    CN105777114A

  • Water-soluble ceramic core and preparation method thereof

    CN106927798A

  • A water-soluble core component and its preparation method

    CN107042309B

  • High-temperature resistance high-strength water soluble core and preparation method thereof

    CN107262661A